Optimalisasi Pengembangan Desa Durian Tinggung Dalam Program Kuliah Kerja Nyata (KKN) - Nila Lestari; Kania Diva Sasmita Pohan; Amanda Aulia Putri Arbain; Muhammad Rizki Ridwan Rambe; Putri Nurul Zulia Lubis; Alya Azizah (Hikamatzu | Journal of Multidisciplinary, 2024)
The Student Community Service Program (KKN) is a higher education curriculum that integrates student learning with community life. The purpose of this study is to optimize the development of Durian Tinggung village through the KKN program. The method used was participant observation conducted by the 29th KKN group at Al Washliyah Muslim Nusantara University Medan for 20 days from July 15 to August 3, 2024. The village development program focused on four main areas: education, religion, environmental hygiene, and health. Activities carried out included private lessons for elementary school students, teaching iqro reading, gotong royong with village officials, installing cleanliness signs, and gymnastics for the elderly and mothers of Durian Tinggung Village. The results showed that all programs implemented received a positive response from the community, especially in the fields of education and health. This KKN program was able to have a significant positive impact on the people of Durian Tinggung Village by improving the quality of education, environmental awareness, and physical health of the village community